If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6 = 0 + 5x Reorder the terms: 6 + 2x = 0 + 5x Remove the zero: 6 + 2x = 5x Solving 6 + 2x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6 + 2x + -5x = 5x + -5x Combine like terms: 2x + -5x = -3x 6 + -3x = 5x + -5x Combine like terms: 5x + -5x = 0 6 + -3x = 0 Add '-6' to each side of the equation. 6 + -6 + -3x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -3x = 0 + -6 -3x = 0 + -6 Combine like terms: 0 + -6 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| 5=t-4s | | -7+6x=5x-15 | | g^2=99990 | | a=8/5(h-96) | | 0j=0 | | 6x-7/5=1 | | 4x-3y(4y+6)=3x | | (9y^2+4y-2)-(-7y+8)= | | 3m^2+m-4=0 | | -6x+1-2x=-55 | | x-7/5=1 | | 4x(3/4) | | 22-6x=14 | | h-h=9 | | l+9=99 | | 9x-3=32x | | 3x+2-5x=2 | | 7x^3+10=5x+20 | | (5x+1)(8x+8)= | | 12/15=/100 | | -9s/5=2 | | x+27853407564307834=73673673467324673674564 | | -0.3e+0.34=2.6e+7.85 | | -5(0.1x+0.2)-1.8=-0.3 | | 0=r^2-43.56 | | 7.50x+1=2.50 | | W^3+2w^2+19+w^2-2w-1= | | 6(7z+1)=6 | | -13=5(1+4*1)-2*1 | | y+2y-9=15 | | 8t^2-20t+5=0 | | 50+10x=30+15x |